Thyroglobulin/thyrotropin ratio for predicting long-term response in differentiated thyroid carcinoma: a retrospective study - De Marchi, Adriano Francisco [UNESP]; de Macedo, Ana Bárbara Trizzotti [UNESP]; Soares, Carlos Segundo Paiva [UNESP]; Bolfi, Fernanda [UNESP]; Iessi, Mariana Riello Gomes [UNESP]; de Oliveira, Cristiano Claudino [UNESP]; Koga, Katia Hiromoto [UNESP]; Moriguchi, Sonia Marta [UNESP]; Tagliarini, José Vicente [UNESP]; da Silva Mazeto, Gláucia Maria Ferreira [UNESP] (Archives of Endocrinology and Metabolism, 2021)
Objective: Thyrotropin-stimulated thyroglobulin (STg) after total thyroidectomy is a prognosis marker for differentiated thyroid carcinoma (DTC). As Tg level is influenced by thyrotropin (TSH), perhaps the STg/TSH ratio is also a prognosis marker for these tumours. We aimed to compare STg/TSH ratio and first STg level in differentiated thyroid carcinoma patients for their ability to predict the long-term response to initial treatment. Methods: This retrospective study evaluated data from 181 DTC patients for first (1st) STg and STg/TSH ratio, at 1-3 months post-total thyroidectomy and before iodine-131 therapy, according to response to initial therapy [Excellent/Indeterminate or Incomplete (Biochemical/Structural)] observed at final evaluation, and with the survival time with excellent/indeterminate response. Results: Cases with incomplete response presented higher STg level [225.13 ± 585.26 ng/mL versus (vs) 20.4 ± 192.9 ng/mL; p < 0.001] and STg/TSH ratio (3.01 ± 7.8 vs 0.27 ± 2.58; p < 0.001). Cutoffs of 5 ng/mL for STg and 0.085 for STg/TSH displayed sensitivities of 76.7% and 76.9%, and specificities of 79.2% and 82.6%, respectively, in predicting response to therapy. Values below these cutoffs were associated with longer survival time in excellent/indeterminate response (140.4 vs 15.9 and 144.6 vs 15.9 months, respectively). Conclusion: STg/TSH ratio has a similar performance to the 1st STg in predicting long-term response to initial therapy.
Keywords: prognosis; thyroglobulin; Thyroid neoplasms